The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s1516-73132004000200006
|View full text |Cite
|
Sign up to set email alerts
|

Formación inicial de profesores de ciencias en Colombia: un estudio a partir de programas acreditados

Abstract: Resumo: Se presentan aquí los resultados de un estudio documental, apoyado en entrevistas a directivos académicos, profesores y estudiantes, de los fundamentos epistemológicos, didácticos y pedagógicos de ocho programas de formación inicial de profesores de ciencias para los niveles básico y medio del sistema educativo colombiano.Unitermos: epistemología; didáctica; pedagogía; formación de profesores; currículo. Abstract: In this paper, we show the results of a study focusing on the epistemological, educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…Since 1988, it is mandatory that teacher education programs meet the accreditation criteria. However, from the research conducted by Gallego, Pe ´rez Miranda, and Torres de Gallego (2004), it can be concluded that only 43 % of all programs meet the accreditation condition. According to data from the National Accreditation Commission, only 8 out of the 76 pedagogy accredited programs are secondary science education programs, and there are no accredited elementary education programs (Comisio ´n Nacional de Acreditacio ´n [CNA], 2010).…”
Section: Science Teacher Education Program Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1988, it is mandatory that teacher education programs meet the accreditation criteria. However, from the research conducted by Gallego, Pe ´rez Miranda, and Torres de Gallego (2004), it can be concluded that only 43 % of all programs meet the accreditation condition. According to data from the National Accreditation Commission, only 8 out of the 76 pedagogy accredited programs are secondary science education programs, and there are no accredited elementary education programs (Comisio ´n Nacional de Acreditacio ´n [CNA], 2010).…”
Section: Science Teacher Education Program Characteristicsmentioning
confidence: 99%
“…The science education area covers between 20 and 30 % of the program and centers its attention on matters related to scientific education, through offering courses that, besides corresponding to science instruction (Biology, Chemistry, Physics), also include other elements that allow for the understanding of science education (e.g., history of science, epistemology of science, research on science education, research on preconceptions). Although the science education component is explicitly included in such science method courses, there exist evidence that most of the subject matter courses include a traditional instruction, centered on teacher lecturer and demonstrative practical work (Gallego et al, 2004). Additionally, the programs lack consensus and discussion about the nature of science and the notion of school science that is promoted during instruction.…”
Section: Science Teacher Education Program Characteristicsmentioning
confidence: 99%
“…Como se puede concluir de los párrafos anteriores, en Colombia, la discusión sobre la importancia de estudiar la práctica pedagógica de profesores en el campo de investigación no es un tema nuevo y hay estudios al respecto desde diferentes perspectivas (Hernández, 2001;Vasco, 1993;Zambrano, 2015) casi siempre desarrollados por grupos de investigación que pertenecen a universidades que ofrecen programas de formación de profesores. No obstante, aún no es claro el impacto que dichas investigaciones han producido en los programas de formación de profesores y en las prácticas pedagógicas en particular (Cofré et al, 2015;Gallego, Pérez y Franco, 2014;Gallego et al, 2004;García et al, 2013;Martínez y Benarroch, 2013;Misas, 2004;Torres, Badillo y Miranda, 2006;Vallejo, 2014;Zambrano, 2015).…”
Section: Contexto Histórico De La Consolidación Del Campo De Investigación En Colombiaunclassified
“…Literature has recognized these coincidences as the principal causes for the prevalence of decontextualized practices focused on the transmission of concepts (Cofré et al, 2015;Gallego et al, 2014;Gallego Badillo et al, 2004;Michel & Neumann, 2016). Thus, finding a solution to this problem implies addressing two critical issues in the science teacher training programs at different levels: i) Find strategies that include NOS, history, and philosophy of science in the learning processes of the discipline (Izquierdo et al, 2016;Moreira, 2004;Salinas et al, 2000;Vallejo, 2014) and ii) develop mentoring programs that contribute to the teachers' practice and generate reflection about it (Elliot, 2000;Vélaz, 2009).…”
Section: Context and Motivationmentioning
confidence: 99%